Efforts to overcome hypoxia condition in Balb/c mouse macrophages after intraperitoneal SRBC immunization (Medical Journal of Indonesia, 2019)
BACKGROUND Activated macrophages require increased oxygen to destroy foreign bodies, leading to an increase in the levels of reactive oxygen species (ROS). Therefore, macrophages would experience hypoxic and oxidative stress conditions at the same time. Thus, this study was aimed to evaluate the mechanism of the activated macrophages to overcoming this dual condition. METHODS The activated macrophages were harvested from the intraperitoneal cavities of 18 BALB/c mice immunized with 2% sheep red blood cells (SRBCs). The macrophage suspension was divided into four groups: control, 24, 48, and 72 hours after-immunization groups. The expressions of hypoxia-inducible factor (HIF)-1α, HIF-2α, and cytoglobin (Cygb), as markers for hypoxic condition, were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA), whereas peroxisome proliferator-activated receptor gamma coactivator (PGC-1α) protein as a marker for mitochondrial biogenesis and aerobic metabolism was measured with ELISA. The analysis of oxidative stress was conducted with the water-soluble tetrazolium salt test. RESULTS The HIF-1α mRNA expression was the highest at 24 hours, whereas the HIF-2α mRNA showed no increased expression during the observation. The Cygb mRNA decreased after 24 hours. The highest expressions of HIF-1α and HIF-2α proteins were detected at 72 hours, whereas the Cygb protein expression increased since 24 hours. The PGC-1α protein expression increased at 72 hours. The WST test showed the highest ROS level at 24 hours.